Advanced Structural Concrete Materials in Bridges (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Many existing and newly constructed bridges are composed of reinforced and prestressed concrete. Advanced concrete materials play an increasingly important role in concrete bridges to facilitate the strengthening and repair of existing bridges, to facilitate a (fast) replacement solution for (part of) an existing bridge, and for the design of new challenging bridge projects. The development of advanced concrete materials and their structural applications is thus an important topic in the built environment.This reprint brings together research and practical applications from the perspective of material scientists and bridge engineers for applications to new and existing bridges.